Harnn Natural Home Spa Business Plan - Kusol, Chompunuch (2008)
Home Spa Partnership is looking for the amount of 50,000 GBP from an investor to invest in the business. The Company offers 20% of its authorised share capital for 17,500 GBP and the preference shares amounting to 32,500 GBP. This amount will be brought into the infrastructures and initial overhead cost for the start-up Thai spa business in the UK under 'Harnn Natural Home Spa' brand.